Maximizing Literature Textbook on “Folkore Appreciation” for the Formation of Student’s Characters - Aida Azizah, Joko Nurkamto, Sarwiji Suwandi, Muhammad Rohmadi (International Journal of Advanced Science and Technology, 2020)
Developing capabilities and forming dignified national character and civilization in order to educate the nation's life is a function of national education which formulated in the National Education System Law. Thus, a powerful tool to form best national character is needed especially in millennial era. This study was designed to describe the role of literary learning "Folkore Appreciation" as a character building tool in the face of the millennial era. Literature learning serves as a means to provide learning, guidance, and direction to students about character, thus students are educated to be well-characterized. To produce such students, at least an effective education strategy is needed to be able to produce students who are in accordance with the expected characteristics. The need for the use of folkore appreciation text books is one of the keys to success in implementing this learning. The folkore appreciation text book provides an important alternative that makes students able to explore and understand character values ​​while they are involved in daily learning activities. The results of the study are expected to show some example of folkore appreciation in textbook.  This is important because the characters formed in students are obtained through the learning they follow. Thus, we hope that the results of this study can be used as an alternative that will support the realization of character students and noble character in facing the millennial era.